Energy Waqf as Islamic Fiscal Innovation: Theoretical Framework and Conceptual Development - Sari, Putri Reno Kemala; Mutia, Galuh Ratna (Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
This study develops a comprehensive theoretical framework for energy waqf as a Shariah-compliant fiscal instrument addressing energy poverty and sustainable development challenges. We synthesize Maqasid al-Shariah principles with contemporary development finance theory to integrate traditional waqf mechanisms with modern energy access strategies. Our contribution is threefold: First, we establish theoretical foundations positioning energy waqf within Islamic fiscal theory. Second, we develop a conceptual framework bridging classical fiqh with development finance architecture. Third, we propose a taxonomy of fiscal waqf instruments for energy poverty alleviation. Through systematic literature review and Maqasid-based analysis, the framework addresses critical theoretical tensions. These include perpetuity requirements versus technological obsolescence, charitable mandates versus fiscal sustainability, and Shariah compliance versus commercial viability. This research provides actionable guidance for policymakers and waqf institutions seeking Shariah-compliant pathways toward universal energy access.